What do we do with ISIS crimes? An analysis of the problems of creating an exclusive tribunal to prosecute them - Joan-Marc Ferrando Hernández (Cuadernos Electrónicos de Filosofía del Derecho, 2023)
As a result of the military defeat of ISIS in 2019, tens of thousands of fighters and their families, including many foreigners –Europeans also– were arrested and interned in prisons and camps in northeastern Syria. The Syrian Democratic Forces (SDF) called on the international community to establish a jurisdictional mechanism to address the accountability of those responsible for crimes committed by ISIS. Since then, different options have been discussed. One of them, which emerged from several European governments reluctant to repatriate ISIS members, was the establishment of an international or hybrid court with the aim of prosecuting only ISIS members. This article reviews the main problems raised by the proposal that affect its legitimacy and legal design.